Diversity, distribution and abundance of oceanic resources around Andaman and Nicobar Islands - Moosamikandy, Sajeevan; Sanadi, Rajashree B (Indian Journal of Fisheries, 2012)
Andaman and Nicobar Archipelago is bestowed with rich oceanic resources. Information on its dynamics is essential to evolve an exploitation strategy and therefore an attempt has been made to understand the diversity, distribution and abundance of oceanic resources around Andaman and Nicobar Islands by utilising exploratory tuna long-line survey data. A total of 29 species of fishes including 15 species of pelagic sharks were recorded during the study. Dominance of pelagic sharks over the target species, i.e., tuna was a major characteristic of the fishery. Drastic reduction in the composition of tuna and sharks towards total catch in recent years was noticed. Hooking rates recorded during different months and at different latitudes are presented. Sharks were dominant between lat. 080 N and 120 N, while no significant pattern was observed in the case of yellowfin tuna. Diminishing trend of hooking rates of tuna and sharks since nineties and replacement of a major share of these resources by uneconomical fishes indicates need for stringent management measures for the conservation of oceanic resources.